Association between food intake patterns and serum vitamin D concentrations in US adults. Issue 5 (14th March 2023) - Ganji, Vijay; Shi, Zumin; Al-Abdi, Tamara; Al Hejap, Dalia; Attia, Yasmine; Koukach, Dalya; Elkassas, Hind
Abstract: The objective of this study was to investigate the association between food patterns and serum vitamin D concentrations in US adults. Data from two cycles of National Health and Nutrition Examination Surveys, 2003–2004 and 2005–2006, were used ( n 6637). Three major food patterns were derived using factor analysis. These three patterns were labeled as meat and processed meat foods (MPF), vegetables, fruit, nuts, and whole grains (VFNW), and sweet, snack, and beverage pattern (SSB). Serum vitamin D was measured with RIA and later standardized to reflect the assay changes over time. In multivariate-adjusted regression analysis, the MPF pattern was significantly, inversely associated with serum vitamin D concentrations ( P < 0·001). However, the relation between the VFNW pattern and serum vitamin D was non-linear ( P < 0·001). There was no relationship between SSB pattern and serum vitamin D in US adults. In conclusion, persons with a high intake of meat and processed meats are associated with lower serum vitamin D concentrations. Reducing processed foods and emphasizing VFNW will be beneficial from a health perspective.